2000
DOI: 10.1046/j.1471-4159.2000.0750606.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin Activity Is Regulated Both by Redox Compounds and by Mutant Familial Amyotrophic Lateral Sclerosis‐Superoxide Dismutase

Abstract: Calcineurin (CN) is a protein phosphatase involved in a wide range of cellular responses to calciummobilizing signals, and a role for this enzyme in neuropathology has been postulated. We have investigated the possibility that redox modulation of CN activity is relevant to neuropathological conditions where an imbalance in reactive oxygen species has been described. We have monitored CN activity in cultured human neuroblastoma SH-SY5Y cells and obtained evidence that CN activity is promoted by treatment with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 64 publications
4
43
0
Order By: Relevance
“…Recently, deregulated cdk5/p35 has been described in mutant SOD1 mice [114] and we have shown that glutamate, a proposed pathogenic mechanism for several neurodegenerative diseases, activates members of the MAPK/SAPK family and causes a slowing of neurofilament transport and increased cell body phosphorylation of neurofilaments [47]. Other studies have shown that SOD1 influences the activity of calcineurin, a neurofilament phosphatase [115,116]. Thus, there is increasing evidence to link known pathogenic processes involved in neurodegenerative diseases with signal transduction cascades that regulate neurofilament phosphorylation.…”
Section: Neurofilament Transport and Neurodegenerative Diseasementioning
confidence: 71%
“…Recently, deregulated cdk5/p35 has been described in mutant SOD1 mice [114] and we have shown that glutamate, a proposed pathogenic mechanism for several neurodegenerative diseases, activates members of the MAPK/SAPK family and causes a slowing of neurofilament transport and increased cell body phosphorylation of neurofilaments [47]. Other studies have shown that SOD1 influences the activity of calcineurin, a neurofilament phosphatase [115,116]. Thus, there is increasing evidence to link known pathogenic processes involved in neurodegenerative diseases with signal transduction cascades that regulate neurofilament phosphorylation.…”
Section: Neurofilament Transport and Neurodegenerative Diseasementioning
confidence: 71%
“…However, the increase in intracellular Ca 2ϩ levels in the G93A mice (31)(32)(33) argues against this hypothesis because the interaction between calcineurin and dynamin is optimal for a small range of intracellular Ca 2ϩ concentration (30). Moreover, calcineurin activity was reported to be either decreased or unchanged in cells overexpressing SOD1 mutants (34,35). Alternatively, the higher level of endocytosis in G93A mice could be due to the activation of GAP-43, a growth-associated protein present in growth cones and synaptic terminals, which has been implicated in nerve sprouting and endocytosis (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…During activity-dependent increases in Ca 2ϩ levels, GAP-43 interacts with rabaptin-5, a protein involved in endocytosis (37). Because GAP-43 is negatively regulated by the phosphatase activity of calcineurin (38), the phosphorylation state of GAP-43 may increase secondarily to possible calcineurin inhibition in G93A mice reported in cells overexpressing SOD1 mutants (34). This hypothesis is supported further by the protective effect of wt SOD on Ca 2ϩ ͞calmodulin-dependent calcineurin inactivation (39).…”
Section: Discussionmentioning
confidence: 99%
“…This phosphatase has been previously described to regulate dephosphorylation of pCREB in hippocampal neurons (43), and calcineurin has been implicated in neuronal apoptosis (19,20) and in neurodegenerative diseases (18,60). However, activation of this phosphatase during oxidative stress is not in line with other reports that superoxide-induced oxidative stress results in an inhibition of calcineurin activity (61)(62)(63) can impinge on different signaling pathways (51); in addition, cell and tissue type may be important in determining these differences.…”
Section: H 2 O 2 Induces a Programmed Neuronal Death Distinct Frommentioning
confidence: 91%